Pengaruh earning per share (eps) dan pertumbuhan investasi serta pertumbuhan total asset terhadap nilai perusahaan - Alissa Oktafianti; Djoko Setyadi; Musdalifah Aziz (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This research was conducted to test the effects of Earning Per Share (EPS) variable, investasion growth, and asset growth of Tobin’s Q. Population is all Automotive and Components companies that listed on the Indonesian Stock Exchange in 2010-2013 period, while samples taken by using purposive sampling method, the sample is selected based on criteria over the study period the company to include of Earning Per Share (EPS) variable, investasion growth, and asset growth. 12 Automotive and Components companies were used as sample. Hypothesis tested by using multiple regression analysis with SPSS version 21.0 for windows. Test results showed that the variable of Earning Per Share (EPS) affect positively and significant on Tobin’s Q. And variable of investasion growth affect negatively and do not have significant on Tobin’s Q. While for variable asset growth affect positively and significant on Tobin’s Q.Keywords: Earning Per Share (EPS), Investasion Growth, Asset Growth, Tobin’s Q.